(untitled) (Journal of Health Sciences, 2014)
Introduction The objective of the paper is to analyze and to assess prevalence of the major behavioral risk factors among adult population (25-64 years of age) in the rural and urban areas in the Federation of Bosnia and Herzegovina (FBIH).Methods Data were taken from cross-sectional population survey on the health status population in the FBIH. To ensure a sample representative for the adult population in the FBIH it was applied the two-stage stratified systematic sample. The survey covered a total of 2735 adult population aged 25-64 years, of which 1087 in the urban areas and 1648 in rural areas.Results. The prevalence of smoking among men in rural areas is significantly higher than among men in urban areas (69% vs. 55%), while the prevalence of smoking among women is higher in urban than in rural areas (45% vs. 31%). There is no statistically significant difference in prevalence of obesity and physical activity according to the age groups among men and women in the urban and rural areas. The frequency of changes in behavior related to acquiring healthy living habits in the rural areas is statistically significant among men and women, while in the urban areas there is no statistical significance among the sexes.Conclusions. The results indicate that there are no significant differences in prevalence of factor risks in urban and rural areas. Prevalence of unhealthy lifestyles is high, and the results should be used to improve standard planning of health promotion-prevention programs.